A Qualitative Review of Learning Methods in Exhibition Design Course - Kukuh Rizki Satriaji; Eljihadi Alfin (ITB Journal Publisher, LPPM ITB, 2022)
The Interior Design Study Program of Institut Teknologi Bandung, Indonesia focuses primarily on design education. The main objectives of this study are teaching how to design and educating designers to be professional. The exhibition design course is an elective course and uses a student-centered learning method. This method is usually adopted to improve student participation. Active student participation is a major element in almost every learning process. This course not only provides knowledge about the ins and outs of exhibition design, but also invites students to solve problems through given assignments. Each assignment is unique and forces the student to role-play as a stakeholder around an exhibition, such as a designer, visitor, content creator, decision maker, etc., to provide different points of view. The student is asked to see the problem from different angles and produce optimal solutions based on their skills and knowledge. The present study was based on observation of the process and results of Exhibition Design courses from two semesters in 2021, during the Covid-19 pandemic. Based on the assignment results and their evaluation, it is shown that this approach can generate student participation and improve the students’ understanding of the subject. The students were always curious about what would happen in the next lecture. All students showed positive learning experiences throughout the course. The general concept of this learning method could be implemented to varying degrees in other courses in interior design schools.